The Second Terrace: Reconnecting with Water and the Vernacular in the Ifugao Rice Terraces - Marchi, Leonardo Zuccaro; Majumder, Shubham; Sabry, Sara (Blue Papers, 2026)
The traditional ecological knowledge (TEK) that is deeply embedded in the Ifugao Rice Terraces offers crucial insights for socio-ecological adaptation and resilience in times of climate change. It helps sustain local biodiversity and supports ecosystem processes while inspiring new design ideas that encourage an epistemological shift that involves integrating traditional knowledge with incremental innovations from the past into future solutions. The Second Terrace Lodge research-by-design project highlights the importance of the Ifugao community’s local landscape and cultural heritage, illustrating how traditional water and land management can be integrated into contemporary architecture and landscape design.
Keywords: Banaue; rice terrace; water systems; vernacular; landscape